On the connection between default logic and DELP - Delladio, Telma (2006)
In this paper, we establish a relation between an argumentation based system: Defeasible Logic Programming (DELP), and a nonmonotonic system: Reiter’s Default Logic. This relation is achieved by introducing a variant of DELP and a transformation that maps default theories to defeasible logic programs. The transformation allows to associate the answers of a DELP Interpreter with the consequences, credulous and skeptical, of the default theory. Thus, this work establishes a link between a well understood nonmonotonic system and a argumentation based system. This link could be studied separately and could be exploited for the development of the latter system.